Perbedaan Efektivitas Daya Antibakteri Ekstrak Daun Mimba (Azadirachta Indica A. Juss) Dibanding NaOCl 2,5% Terhadap Enterococcus Faecalis (The Difference of Antibacterial Effectiveness of Neem Leaf Extract (Azadirachta Indica A. Juss) Than NaOCl 2,5% Against Enterococcus Faecalis) - Setian Fitri Sayekti; Agus Subiwahyudi; Edhie Arif Prasetyo (Conservative Dentistry Journal, 2016)
Background. Enterococcus faecalis is often found in persistent endodontic infection. Its high prevalence, about 24-77%, is due to resistance and virulence of these bacteria. NaOCl is commonly use as irrigation material, but it has toxicity effect and can irritate periapical tissues. Therefore, some studies to find natural materials that have antibacterial properties as an alternative root canal medicament need to be done. Neem (Azadirachta Indica A. Juss), also known as wonder tree for centuries has antibacterial properties, proven in the preliminary study which has been done that the MIC (Minimum Inhibitory Concentration) is 65% and MBC (Minimum Bactericidal Concentration) is 70%. Purpose. The aim of this study was to compare the effectiveness of antibacterial activity of the Neem leaf extract (Azadirachta Indica A. Juss) than NaOCl 2,5% against Enterococcus faecalis. Methods. This study is an experimental labolatory with post test only control group design usingEnterococcus faecalis ATCC 29212. Agar diffusion test was used to check the antimicrobial activity of 65% Neem leaf ectract, 70% Neem leaf ectract and NaOCl 2,5% by measuring the inhibition zone diameter of each treatment.Result. Diameter of bacterial inhibition zone formed Neem leaf extract is greater than NaOCl 2,5%. Conclusion. The antibacterial activity of Neem extract is greater than NaOCl 2,5% against Enterococcus faecalis.